Chikungunya: educación y prevención como pilares fundamentales para enfermedad sin cura - Acosta H., Nicolás; Tobar U., Daniel; Olivares C., Roberto; Dabanch P., Jeannette; Norambuena G., Mackarenna (Revista Hospital Clínico Universidad de Chile, 2019)
Chikungunya virus is an alphavirus, member of the Togaviridae family, first discovered in Africa in 1952. Since then it caused sporadic outbreaks in Africa and Asia, but since 2000, outbreaks had been more frequent, being identified in Europe, America and the Caribbean. Chikungunya virus can cause chronic and incapacitating arthralgia, with an important morbidity, being considered as a relevant re-emerging public health problem. This review intends to update our knowledge in epidemiology, transmission, pathogenesis, treatment and vaccination strategies of Chikungunya virus.